Designing AI chat-bots and User Assisted Systems in Business Applications - Creating Guidelines for a Graphical Interface - Olsson, Linnea; Lu, Jenny (My University, 2024)
This thesis investigates the impact of graphical interfaces on AI chatbots and User Assisted Systems (UAS) within business applications, with a particular focus on designing interfaces for the CANEA ONE platform. The primary research questions revolve around optimizing customer acceptance, usage, and satisfaction of AI chatbots in business contexts, while also addressing key considerations and challenges in their design. By adopting a user-centered design approach, which includes design sprints and stakeholder engagement, the study integrates literature review, qualitative and quantitative data collection, and prototyping phases. The resulting high-fidelity prototype underwent rigorous user testing, serving as the foundation for the development of comprehensive guidelines. These guidelines successfully outline best practices for designing chatbots and UAS tailored specifically to business applications.
Keywords: AI Chatbot; Design Guidelines; User-Centered Design; Chatbot interface; User Assisted System